Ahmedabad municipal bond: lessons and pointers - Vaidya, Chetan; Johnson, Brad (2001)
The Rs. 1,000-million municipal bond issues of the Ahmedabad Municipal Corporation was a landmark in that it was the first such instrument issued in India without a state guarantee. The proceeds of the issue were to be used to fund the city's water supply and sewerage project. This spaper describes the groundwork that was prepared for the bond issue, the conception and financing pattern of the project, and the issuance of the municipal bonds. The authors argue that the technical framework set up for the AMC bonds can act as a blueprint for future development initiatives. - Reproduced
Keywords: Local government